The trafficking of women and children in Nigeria an analysis of the new anti-trafficking legislation and its application - Rabiu Sani Shatsari, (Fakulti Undang - Undang, 2010)
Human trafficking refers to the use of force, coercion or fraud to move people, mostly women and children, within or across national borders, for the purpose of labour or sexual exploitation. Human trafficking poses global challenges relating to human rights, labour and security. Every country is affected by the problem of human trafficking although the scale of it may be higher in one country than in another. This article analyses the legal framework for dealing with the trafficking of women and children in Nigeria. It does so by exploring the various anti-trafficking measures contained in the Nigerian Trafficking in Persons (Prohibition) Law Enforcement and Administration Act 2003 as amended and recommending further new amendments to it. This article begins with a background information on the problem of human trafficking in the global arena and in Nigeria; gives an overview of the 2000 UN Protocol on Trafficking; highlights the U.S. Minimum Standards on the combat against human trafficking with particular attention to the objectives of the annual U.S. TIP Report and uses the Three P’s approach to discuss the provisions of the TIPPLEA 2003 Act and the various efforts of the Nigerian antitrafficking agency, NAPTIP, to implement the provisions of the Act. The article concludes with an appreciation of the efforts of Nigeria to tackle human trafficking and a call for greater attention to the problem by for instance plugging some of the gaps in the law